Hydroxyapatite/Graphene Composite Anticorrosion Coating on Ti-6Al-4V: Fabrications and Trend - Zufar Maulana; Falihah Balqis; Muhammad Irsyad; Alhadi Kasyfi; Ekavianty Prajatelistia; Nurrochman, Andrieanto (UPT Publikasi Ilmiah UNISBA, 2025)
Orthopedics implants have become more crucial for bone replacement as the need for bone replacement increases. Titanium alloy Ti-6Al-4V is widely used as an orthopedic implant due to its high biocompatibility and superior mechanical properties. However, it has several serious drawbacks, such as low corrosion resistance. In order to overcome this demerit, coatings should be applied. Hydroxyapatite, a mineral similar to bone composition, is a good candidate for this purpose. By compositing hydroxyapatite with graphene, the mechanical properties and adhesion of the coating are enhanced. Various coating methods are employed to fabricate this composite coating. This work summarizes and discusses trends, fabrication techniques, and the future perspectives of hydroxyapatite/graphene as a Ti-6Al-4V implant coating.